Pemberian Enzim Papain Dosis Berbeda dalam Pakan Komersial pada Pemeliharaan Benih Ikan Bandeng (Chanos chanos, Forsskal) - Akmal, A; Marwan, M; Bahri, Syamsul; Mundayana, Yuani; Supito, S; Rahmi, R (Journal Galung Tropika, 2021)
Feed is one of the problems in the milkfish (Chanos chanos, Forsskal) hatchery. The commercial feed contains protein that fish have not optimally utilized. One solution to increase protein absorption is the addition of papain enzymes. This engineering aims to analyze the application of papain enzyme in commercial feed on milkfish fry on survival, growth, feed efficiency, and RNA/DNA ratio. The test fish were milkfish fry with an average weight of 0.0003±0.0 g/head with a density of 15 fish/L. The engineering method used a completely randomized design method with 4 treatments and 3 replications. The treatments tested were administering papain enzyme in commercial feed dosages: 0.5%; 1.50%; 2.25%; and control. The engineering results showed that the administration of papain enzymes with different doses had a significant effect (P<0.05) on the relative growth rate but had no significant effect (P>0.05) on feed utilization efficiency, survival rate, and RNA/DNA ratio of milkfish fry. The highest relative growth rate value was obtained at a dose of 1.5%, which was 4.77±0.06%/day, while the lowest was found at a dose of 0.0% (control), which was 2.86±0.65%/day. The best feed efficiency value during engineering was obtained at a dose of 0.50% papain enzyme treatment of 78.0±29.3%. The highest survival rate in control was 34.6±3.70%, while the lowest was at a dose of 2.25% at 24.9±0.68%. Furthermore, the highest RNA/DNA ratio was obtained at a 1.50% papain enzyme dose of 0.85±0.14/mL, while the lowest was in control with an RNA/DNA ratio of only 0.76±0.06/mL. Water quality parameters during engineering are still within a reasonable range for milkfish fry maintenance.